Belom Bahadat Sebagai Strategi Kultural Berbasis Pendidikan Multikultural Dalam Mitigasi Kekerasan Terhadap Perempuan dan Anak Pada Masyarakat Dayak Ngaju - Handoko Handoko; I Wayan Suasta; I Wayan Salendra; I Gusti Agung Dharmawan (Jayapangus Press, 2026)
Violence against women and children is still a social problem that requires a mitigation strategies. The solution was lies in local wisdom, such as that of Belom Bahadat in the Dayak Ngaju community, which has not been widely studied. This research aims to analyze the practice of Belom Bahadat values, the role of customary institutions as mechanisms of social control and community-based protection, and their integration with multicultural education. A qualitative, descriptive-interpretive approach was chosen for the research. Research data were obtained from two sources: primary data from semi-structured interviews and participatory observation, and secondary data from customary documents, local archives etc. To ensure the validity of the research data, triangulation of sources and methods, member checks, and the preparation of trial audits. The research data were then analyzed through data reduction, data presentation, and conclusion drawing. The results of the study show that Belom Bahadat functions as a moral regulatory framework that affirms human dignity, gender respect, and communal responsibility; the preventive mechanism is seen in the internalization of values through communal life (Huma Betang) and socialization by customary institutions, while the restorative mechanism is manifested through customary deliberation and the imposition of symbolic and material sanctions. The integration of Belom Bahadat’s values with a multicultural education approach also shows that local value systems can be operationalized in educational practices within families, schools, and communities. This research provides implications for adopting a violence-mitigation model based on local wisdom that can be adapted and replicated in similar contexts.